DESAIN OPTIMASI ABSENSI APLIKASI ANDROID DENGAN MENGGUNAKAN SIMPLE RANDOM SAMPLING - Sri Utami; Yuni Fitriani; Bambang Junadi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Attendance gives the impression of a system that is familiar but if there is data confusion it will affect other systems, be it payroll or appraisal. With attendance, we can determine the next step, so the author thought to prove whether using an attendance application helps staff in maintaining their attendance data. In absence permits, you can directly go through the application, so that everything is recorded and can be continued for salary calculations. Optimization of online-based applications is designed to be compatible with every gadget of integrity guidance agency staff. To find out the validation in terms of the functionality of the designed application, a random target was carried out by the author making the questionnaire as a medium so that staff could obtain assessment data after using the attendance application. The data is processed based on two variables with a total of 20 respondents, processed to find out the expected frequency cell value, and analyzed to make it look significant so that the author's hypothesis can be proven accepted. With the simple random sampling method this research was carried out, it is hoped that it can be further developed in the future with different methods.